Implementation of Base64 Algorithm for Securing SMS on Smartphones - Ros Minarni (The IJICS (International Journal of Informatics and Computer Science), 2018)
In this study the authors used the base64 algorithm, the Base64 algorithm is one algorithm for encoding and decoding a data using the ASCII format, which is based on 64 base numbers or can be said to be one of the methods used to encode (encode) binary data. The results obtained from the ROSMINARNI text message example were encoded with base64 into Uk9TTUlOQVJOSQ, the application of the Base64 algorithm to secure sms messages was done by creating a cryptographic application with the help of the Java Android programming language, the process of securing SMS messages using the Base64 algorithm can run well and produce difficult ciphertext known by ordinary people